Personality Traits and Cardiotoxicity Arising From Cancer Treatments: An Hypothesized Relationship - Durosini, Ilaria; Mazzocco, Ketti; Triberti, Stefano; Russo, Gaetano Alessandro; Pravettoni, Gabriella (Frontiers in Psychology, 2021)
Thanks to the evolution in medical and pharmaceutical research, to date, the number of cancer treatments is increasingly on the rise. Despite this, several side effects related to cancer treatments can exacerbate patients’ physical and psychological conditions, such as cardiotoxicity. Over the years researchers have explored the possible relationship between psychological variables and physical diseases. Even though some authors examined the relationship between personality and specific diseases, no scientific attention has been paid to the role of personality in the development of cardiotoxicity arising from cancer treatments. Yet this is an important objective, given that determining whether personality influences cardiac toxicity of anticancer treatments could inform the processes by which stable psychological factors influence health. This contribution summarizes and analyzes the available scientific evidence about the association between personality and main cardiotoxicity-related-diseases of anticancer therapies, including cancer and cardiovascular diseases, in order to sketch a hypothetical model of the relationship between personality traits and cardiotoxicity.